Micronutrient Adequacy in Preschool Children Attending Family Child Care Homes - Cuadrado-Soto, Esther (Nutrients, 2019)
Limited data is available on the micronutrient intake and adequacy in preschool children enrolled in family child care homes (FCCH). The goal of this paper is to describe the micronutrient adequacy relative to age-specific recommendations of preschool-aged children (aged 2–5 years) attending FCCH in Rhode Island (RI). Dietary data among younger preschoolers (aged 2–3 years), n = 245) and older preschoolers (aged 4–5 years), n = 121) in 118 RI FCCH (N = 366 children) were analyzed. Nutrient adequacy was assessed as the amount of nutrient per 1000 kcal of the diet that would meet the Institute of Medicine nutrient requirements (critical nutrient density), and it was compared to the observed nutrient densities of the children. The sodium:potassium ratio was also calculated. For most micronutrients, the observed density met or exceeded the recommendation, meaning the children’s intake was adequate. However, a high proportion of children had nutrient densities under the recommendation for vitamins D, E, K, and potassium (86.1%, 89.1%, 70.8%, and 99.2% of children, respectively). The mean vitamin B12, potassium, and zinc densities were statistically higher in younger vs. older preschoolers (p < 0.05 for all). Low densities in calcium and vitamins K and B5 were more frequent in older children vs. younger children (p < 0.05). In addition, older preschoolers had a higher sodium:potassium ratio than younger children (p < 0.05). The micronutrient intake density was adequate for most nutrients. However, intake of some nutrients was of concern. Further attention to training and compliance in FCCH may improve the diet quality of those cared for in these settings.